Digenean parasites of Cyphocharax platanus (Günther, 1880) (Characiformes: Curimatidae) from the lower Uruguay River, downstream Salto Grande dam, Uruguay (FAVE Sección Ciencias Veterinarias, 2016)
Seventy six specimens of Cyphocharax platanus were collected downstream Salto Grande dam, lower Uruguay River, Uruguay, between August 2012 and June 2013 and examined for digenean parasites. Three digenean taxa were identified: Saccocoelioides spp. (Haploporidae), Zonocotyle bicaecata (Zonocotylidae) (both adult in intestine) and Sphincterodiplostomum musculosum (Diplostomidae) metacercariae inside eyes. We found that 69.7% of examined fish were parasitized by at least one digenean taxon. Saccocoelioides spp. showed highest values of prevalence, mean intensity and mean abundance (43.4%, 5.45, and 2.37, respectively) of infection throughout the study than Z. bicaecata (28.9%, 1.32 and 0.38, respectively) and S. musculosum (13.2%, 2.80 and 0.37, respectively). Saccocoelioides spp. and S. musculosum showed an aggregated distribution pattern, while Z. bicaecata presented a random distribution in the host population. No significant differences in infection indexes of any digenean taxa in relation to host sex were found, and only Saccocoelioides spp. showed a significant association with host size, being more frequent in small fish. The infection indexes of the two intestinal digeneans (Saccocoelioides spp. and Z. bicaecata) were not significantly associated. These are the first records of Saccocoelioides spp. and Z. bicaecata from C. platanus in the Uruguay River, and the finding of S. musculosum metacercariae is a new host-parasite relationship.
Keywords: Cyphocharax platanus; parasites; Digenea; Uruguay river; Salto Grande dam